Social imaginaries about initial education male teacher on Comas district, Lima, Perú - Zapata Cano, Juan José (2019)
This investigation seeks to interpret the social imaginaries about Initial Education male teacher on Comas district, Lima, Perú on 2018. This study pose since qualitative focus, phenomenological design through description of narratives on that community, with semi-estructured interview, getting this information about representations or thoughts socially accepted and extended that are build aroud a rare situation on this education level, so that it offers evidence about the influence of those peceptions in the exercise and teaching practice.